PENGARUH LINGKUNGAN KERJA, MOTIVASI DAN KOMPETENSI PROFESIONAL GURU TERHADAP KINERJA GURU DI SEKOLAH DASAR NEGERI 49 SOMPONG KECAMATAN TELLU LIMPOE KABUPATEN SINJAI - Suardi; Mulyadi, Edi; Hardian, Dafyar Eliadi (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2025)
This study aims to analyze the influence of the work environment, motivation, and professional competence on the performance of educators at Sompong 49 Public Elementary School, Tellu Limpoe District, Sinjai Regency. The background of this study is the importance of internal and external factors that influence the quality of educators in carrying out their professional roles. The study was conducted using a quantitative approach through a survey method. All 31 teachers at Sompong 49 Public Elementary School were selected as respondents using a total sampling technique. The research instrument was a 39-item questionnaire that had been tested for validity and reliability. Data were analyzed using multiple linear regression with the assistance of SPSS version 20. The analysis results indicate that working conditions significantly contribute to improving educator performance, with a calculated t value of 2.112 > t table 2.048 and a significance level of 0.04. The motivation variable showed results that require further review because, although the calculated t value is < t table, the significance value is < 0.05. Professional competence was shown to have a significant influence, with a calculated t value of 3.387 and a significance level of 0.02. Collectively, the three independent variables significantly contribute to performance quality, as evidenced by the calculated F of 5.484 > Ftable 3.35, with a significance level of 0.004. The coefficient of determination (R²) of 0.379 indicates that 37.9% of the variation in performance is explained by the research variables, while the remainder is influenced by factors outside the model. These findings confirm that improving teacher performance can be achieved through creating a conducive work environment, providing motivational support, and continuously developing professional competencies. This study recommends that school principals and stakeholders pay attention to these aspects as an effort to improve the quality of education at the elementary school level. Keywords: Work Environment, Motivation, Professional Competence, Teacher Performance.